Pengaruh Keputusan Investasi Dan Kebijakan Dividen Terhadap Nilai Perusahaan Sektor Pertambangan Minyak dan Gas Bumi (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of investment decisions and the influence of dividend policies on firm value in oil and gas mining companies listed on the IDX. The population in this study are Oil and Gas Mining Sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021, totaling 18 companies, with a sample of 5 companies. The analysis technique used in this study is a multiple linear regression analysis technique using the SPSS 23 test tool.